القيادة الرقمية على الاستعداد للتغيير في قطاع التعليم العالي في فلسطين: نموذج مقترح: THE IMPACT OF DIGITAL LEADERSHIP ON READINESS FOR CHANGE IN THE HIGHER EDUCATION SECTOR IN PALESTINE: A PROPOSED MODEL - Abuajwa, Abdallah H.; Ali Al-Tahitah, Ali Nasser; Abdul Muthaliff, Mohamed Mihlar (I-iECONS e-proceedings, 2023)
: تُعد القيادة الرقمية من أهم المفاهيم الإدارية الحديثة التي تساهم في تطوير وتحسين وضمان استمرار للمنظمات في أداء رسالتها ومهامها على اختلاف أهدافها وتصنيفاتها، وهي تهدف بشكل رئيس إلى توفير البيئة المناسبة لإحداث تغييرات تكنولوجية في بيئة العمل هدفها التعامل مع متطلبات العصر التكنولوجي الحالي من خلال توظيف التكنولوجيا الحديثة من أجل تطوير وتحسين العمل ورفع كفاءة العاملين مما يرفع ذلك من كفاءة هذه المؤسسات لاسيما في الوقت الذي أصبح استعمال التكنولوجيا من الأولويات في ظل التغيير المتسارع في بيئة المنظمات، وعليه تهدف هذه الورقة إلى تسليط الضوء على مفاهيم القيادة الرقمية وكذلك علاقتها بالاستعداد للتغيير وواقعها في مؤسسات التعليم العالي بغزة - فلسطين، من خلال مراجعة أدبيات الدراسات السابقة ذات العلاقة بموضوع الدراسة، هذا ويتكون مجتمع الدراسة من العاملين في هذه المؤسسات ، وعينة الدراسة هم العاملين ذوي المسميات الإشرافية في الفترة الزمنية 2020 -2023 ، وعليه سيتم اختيار عينة عشوائية بسيطة من المبحوثين كما سيتم استخدام برنامج (SPSS) لمناقشة واختبار الفرضيات ونموذج الدراسة، وسيتم الاعتماد على المنهج الوصفي التحليلي لإجراء الدراسة لملائمته لأغراض وطبيعة الدراسة وأهدافها، حيث ستستخدم الاستبانة كأداة رئيسة لجمع البيانات بغرض تحليلها ومعالجتها وصولاً للنتائج المرجوة، ومن المتوقع أن تجد الدراسة الحالية تأثير إيجابي للقيادة الرقمية على الاستعداد للتغيير في مؤسسات التعليم العالي بغزة – فلسطين. وان تشكل هذه الدراسة مرجع حقيقي للمؤسسات محل الدراسة. Digital leadership is one of the most critical modern management concepts contributing to the development, improvement, and sustainability of organizations in fulfilling their missions and tasks across different goals and classifications. Its primary aim is to create a suitable environment for introducing technological changes into the work environment, addressing the current technological requirements by employing modern technology to enhance and develop work processes and boost the efficiency of employees. This elevates the efficiency of institutions, especially in a time when the use of technology has become a priority amid rapid changes in the organizational environment. However, this paper sheds light on the concepts of digital leadership and its relationship with change readiness in Palestinian higher education institutions in Gaza. It does so by reviewing relevant literature and conducting a study that involves individuals working in these institutions, specifically those holding supervisory positions from 2020 to 2023. The study employs a simple random sample of participants and utilizes the SPSS software to analyze and test hypotheses. The study adopts a descriptive analytical methodology that aligns with its objectives and nature. The primary data collection tool is a questionnaire used to gather, analyze, and process data to reach the desired results. The current study is expected to reveal a positive impact of digital leadership on change readiness in Palestinian higher education institutions in Gaza, serving as a valuable reference for these institutions.